Perceptions of doctors and nurses of International Hospital Kampala (IHK) – Out Patient Department and Emergency Unit (OPD&EU), regarding introduction and use of the South African Triage Scale (SATS) - Mulindwa, Francis (Stellenbosch : Stellenbosch University, 2016)
Thesis (MFamMed)--Stellenbosch University, 2015.